2016
DOI: 10.1038/srep23121
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial polymer PHMB enters cells and selectively condenses bacterial chromosomes

Abstract: To combat infection and antimicrobial resistance, it is helpful to elucidate drug mechanism(s) of action. Here we examined how the widely used antimicrobial polyhexamethylene biguanide (PHMB) kills bacteria selectively over host cells. Contrary to the accepted model of microbial membrane disruption by PHMB, we observed cell entry into a range of bacterial species, and treated bacteria displayed cell division arrest and chromosome condensation, suggesting DNA binding as an alternative antimicrobial mechanism. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
207
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(219 citation statements)
references
References 40 publications
(54 reference statements)
8
207
0
4
Order By: Relevance
“…Recent research further supports the interaction with bacterial membranes as the mode of action for PHMB, stating that it disturbs the first layer of the membrane lipid bilayer (Chadeau et al, 2012) by electrostatic as well as hydrophobic interactions and dehydration (Souza et al, 2015). However, a new study also strengthened the hypothesis of additional mechanisms of the bactericidal effect of PHMB based on the interaction of the infiltrated substance with bacterial chromosomes (Chindera et al, 2016). In this work, PHMB was shown to enter bacterial cells and condense chromosomes as well as arrest cell division, ultimately leading to the death of treated bacteria.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent research further supports the interaction with bacterial membranes as the mode of action for PHMB, stating that it disturbs the first layer of the membrane lipid bilayer (Chadeau et al, 2012) by electrostatic as well as hydrophobic interactions and dehydration (Souza et al, 2015). However, a new study also strengthened the hypothesis of additional mechanisms of the bactericidal effect of PHMB based on the interaction of the infiltrated substance with bacterial chromosomes (Chindera et al, 2016). In this work, PHMB was shown to enter bacterial cells and condense chromosomes as well as arrest cell division, ultimately leading to the death of treated bacteria.…”
Section: Discussionmentioning
confidence: 98%
“…Also, Chindera et al (2016) demonstrated that despite an uptake of PHMB into several mammalian cell lines, no transition into nuclei occurs owing to entrapment of PHMB in endosomes. As a consequence, PHMB displays an excellent combination of bactericidal efficacy and low cytotoxicity to mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guanidine-based antimicrobials were thus believed to have low toxicity to humans (Ikeda et al, 1983(Ikeda et al, , 1984. However, recent accounts have reported PHMB penetrating mammalian cells and interacting with chromosomes, raising concerns about health hazards from guanidine-based antimicrobials (Allen et al, 2004(Allen et al, , 2006Chindera et al, 2016;Firdessa et al, 2015).…”
Section: Biocidal Properties Of Phmg-pmentioning
confidence: 99%
“…PHMB exhibits bacteriostatic at low concentrations (10 mg/L). It can slightly damage the cell membrane, interact with bacterial DNA, and inhibit bacterial proliferation [2,4]. No one resistant microorganism mutant has been reported after several decades of extensive use [5].…”
mentioning
confidence: 99%